2018
DOI: 10.1136/bmjopen-2017-019683
|View full text |Cite
|
Sign up to set email alerts
|

Engaging older people in an internet platform for cardiovascular risk self-management: a qualitative study among Dutch HATICE participants

Abstract: ObjectivesTo study older peoples’ experiences with an interactive internet platform for cardiovascular self-management, to assess which factors influence initial and sustained engagement. To assess their views on future use within primary care.DesignQualitative semistructured interview study, with thematic analysis.SettingPrimary care in the Netherlands.ParticipantsPeople ≥65 years with an increased risk of cardiovascular disease who used the ‘Healthy Ageing Through Internet Counselling in the Elderly’ interne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
148
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(152 citation statements)
references
References 26 publications
(29 reference statements)
3
148
0
1
Order By: Relevance
“…The intervention platform was carefully designed using an iterative process involving the end users throughout development, leading to good usability, as confirmed in a Intervention Control qualitative substudy. 17,18,25 Our pragmatic multicomponent approach makes it difficult to disentangle effects of different components of the intervention, particularly to differentiate between the effects of the application itself and of the coach. A limitation of our primary outcome is the difficulty to establish its clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The intervention platform was carefully designed using an iterative process involving the end users throughout development, leading to good usability, as confirmed in a Intervention Control qualitative substudy. 17,18,25 Our pragmatic multicomponent approach makes it difficult to disentangle effects of different components of the intervention, particularly to differentiate between the effects of the application itself and of the coach. A limitation of our primary outcome is the difficulty to establish its clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…During the screening visit, blood pressure and anthropometrics were assessed. Full study logistics and procedures are provided in the appendix (pp [25][26]. Medical history and medication use were registered.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Insight into the acceptability of a preventive Internet intervention in older European adults will be provided by the recently completed Healthy Ageing Through Internet Counselling in the Elderly trial [26]. Initial qualitative results suggest that human support may be crucial for the success of this kind of intervention in older age groups [27].…”
Section: Discussionmentioning
confidence: 99%
“…participated in classes, not engagement outside of classes), (Coley et al, 2019;Ngandu et al, 2015) individually and combined, and these findings are based mainly on active supervision of study staff. Research staff supervision and involvement in behavioral interventions is known to increase intervention participation (adherence) (Ligthart et al, 2015;Van Middelaar et al, 2018). Our reported adherence may differ from that of the FINGER trial because 1) we reported on-going adherence (post-intervention engagement) in intervention components outside of structured in-person sessions and 2), we used a mixture of direct observation (BrainHQ TM portal report and calendar completion) and partner report to determine post-intervention adherence.…”
Section: Discussionmentioning
confidence: 97%